KAJIAN ANALISIS DISKRIMINAN MENGUKUR LOYALITAS PELANGGAN TOKO BUKU SUCI KUPANG - Thom W. A. Isliko (Universitas Nusa Cendana, 2016)
Customer Loyalty is an expectation of all business. Many efforts will be done to achieve thatobjectives. Serious problem would be faced is how to investigate the impact of efforts towardimproving Customer Loyalty. Using of Discriminant Analysis is one of the tool which can be solvedthat problem. Without the set of analysis technology, it is impossible to obtain quality decisionrapidly, efficiently and effectively in business.Keywords : Loyalty, Customer Dimensionality, Discriminant Analysis